ORGANIZATIONAL AND TECHNOLOGICAL SOLUTION TO GAIN BASED ON THE FOUNDATION SUPERSTRUCTURE FLOOR IN THE PROCESS OF RECONSTRUCTION THE HOTEL "DNIPRO" IN ZAPOROZHYE - , І. Д., Р. В., А. І. (Municipal economy of cities. Series: «Economy science», 2013)
The questions of foundation base reinforcement of building of Dnepr hotel are considered at reconstruction with floor superstructure in Zaporozhye. Base reinforcement is executed by means of soil reinforcement by horizontal soil-cement elements on boring mixing technology.